Humanities in the spotlight. Interdisciplinary perspectives (Presa Universitară Clujeană, 2025)
The volume Humanities in the Spotlight. Interdisciplinary Perspectives is a collection of academic works from diverse but intertwined fields, namely approaches from the humanities, education, linguistics, literature, and social sciences. This volume brings together fifteen original contributions by distinguished authors affiliated with higher education institutions in Romania and abroad. Their studies show how valuable interdisciplinary research is and how important these fields are in a global, constantly changing context.